2019
DOI: 10.19128/turje.489226
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki erken çocukluk eğitimi üzerine yazılmış lisansüstü tezlerin bir içerik analizi

Abstract: This study aims to investigate the descriptive characteristics, research topics and methodological procedures of master's theses and doctoral dissertations regarding early childhood education in Turkey. Within the scope of the current study, 931 Master's theses and 171 doctoral dissertations were analyzed according to university, institute, department, publication year, academic title of the advisor, research topic, sample group, location in which the study took place, research setting of the study, type of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(13 reference statements)
4
3
1
Order By: Relevance
“…In the findings of their study, the most frequently seen research topics were socialemotional skills/behaviors, language/foreign language education, play in preschool, and science teaching/environment. Additionally, similar to the findings of studies from theses and dissertations (Ahi & Kıldan, 2013;Demirtaş İlhan & Tantekin Erden, 2019), the findings in the current study showed that physical development was the least common subject within the category of developmental subjects amongst articles examined (n = 8).…”
Section: Research Topics Of the Articlessupporting
confidence: 89%
See 4 more Smart Citations
“…In the findings of their study, the most frequently seen research topics were socialemotional skills/behaviors, language/foreign language education, play in preschool, and science teaching/environment. Additionally, similar to the findings of studies from theses and dissertations (Ahi & Kıldan, 2013;Demirtaş İlhan & Tantekin Erden, 2019), the findings in the current study showed that physical development was the least common subject within the category of developmental subjects amongst articles examined (n = 8).…”
Section: Research Topics Of the Articlessupporting
confidence: 89%
“…Educational subjects were found to be the prevailing choice in approximately 40% of the articles. This finding parallels other studies which examined theses and dissertations from early childhood education (Ahi & Kıldan, 2013;Demirtaş İlhan & Tantekin Erden, 2019). Amongst the educational subjects, special education/inclusion (n = 43) and science education (n = 30) were the two most commonly seen subjects.…”
Section: Research Topics Of the Articlessupporting
confidence: 87%
See 3 more Smart Citations